Case Marking in Hindi as the Weaker Language - Montrul, Silvina; Bhatia, Archna; Bhatt, Rakesh; Puri, Vandana (Frontiers in Psychology, 2019)
Does language dominance modulate knowledge of case marking in Hindi-speaking bilinguals? Hindi is a split ergative language with a rich morphological case system. Subjects of transitive perfective predicates are marked with ergative case (-ne). Human specific direct objects, indirect objects, and dative subjects are marked with the particle -ko. We compared knowledge of case marking in Hindi-English bilinguals with different dominance patterns: 23 balanced bilinguals and two groups of bilinguals with Hindi as their weaker language: 24 L2 learners of Hindi with age of acquisition (AoA) of Hindi in adulthood and 26 Hindi heritage speakers with AoA of Hindi since birth) in oral production and acceptability judgments. The balanced bilinguals outperformed the English-dominant bilinguals; the L2 learners and the heritage speakers, who showed similar lower command of the Hindi case marking system, with the exception of –ko marking as a function of specificity with direct objects. We consider how dominant language transfer, age of acquisition of Hindi, and input factors may explain the acquisition and knowledge of morphology in Hindi as the weaker language.